2020
DOI: 10.1177/1559325820909778
|View full text |Cite|
|
Sign up to set email alerts
|

Benefits of Low-Dose CT Scan of Head for Patients With Intracranial Hemorrhage

Abstract: Objectives: For patients with intracranial hemorrhage (ICH), routine follow-up computed tomography (CT) scans are typically required to monitor the progression of intracranial pathology. Remarkable levels of radiation exposure are accumulated during repeated CT scan. However, the effects and associated risks have still remained elusive. This study presented an effective approach to quantify organ-specific radiation dose of repeated CT scans of head for patients with ICH. We also indicated whether a low-dose CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, most studies discussing radiation risks in children were published more than 10 years ago or are based on data obtained even before the millennium. The newer generation of CT scanners can perform low-dose CT protocols with reduced radiation exposure of 45–50% [ 23 , 24 ]. Therefore, future studies should investigate the risks of radiation exposure in children after low-dose CT scans for reasonable comparisons with the benefits and disadvantages of whole-body MRI after high-energy trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most studies discussing radiation risks in children were published more than 10 years ago or are based on data obtained even before the millennium. The newer generation of CT scanners can perform low-dose CT protocols with reduced radiation exposure of 45–50% [ 23 , 24 ]. Therefore, future studies should investigate the risks of radiation exposure in children after low-dose CT scans for reasonable comparisons with the benefits and disadvantages of whole-body MRI after high-energy trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Later, there have been some studies where experts have analyzed the application of low-dose CT scanning in the detection of a cerebral hemorrhage. e results indicate that the low-dose CT scan can achieve the same effect as routine dose CT scan in the examination of patients with cerebral hemorrhage and is conducive to reducing the radiation impact on patients, so it has a good application value [8,21]. A recent meta-analysis has shown that, in the low-dose CT imaging of patients with atherosclerotic subarachnoid hemorrhage, if the radiation dose is reduced to 40% of the original dose level, the accuracy of the diagnosis of cerebral perfusion injury will not be affected [7].…”
Section: Discussionmentioning
confidence: 91%
“…At the present stage, the main means of examination for suspected patients with intracerebral hemorrhage is a craniocerebral computed tomography (CT) scan. However, as the condition of intracerebral hemorrhage is prone to recurrence and changes, multiple scans of intracerebral hemorrhage patients are needed to determine the condition of the disease, so that the clinical treatment plan can be changed [7,8]. e images scanned by CT with the features of high resolution, clear pixels, and no artifacts can provide clear diagnostic evidence for the clinical treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the subject image quality assessment (1) severity of background noise, (2) severity of imaging artifacts, and (3) clarity of demonstration of lesions and anatomical structure were taken into account. 18 , 19 Five grades were designed to each factor, with 5 representing the best quality ( Table 1 ). The scores from the 3 domains determined by the 2 neuroradiologists were then averaged to generate an overall score for image quality.…”
Section: Methodsmentioning
confidence: 99%